2021
DOI: 10.1186/s12866-021-02105-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenomic profiling of a novel sibling species within the Scedosporium complex in Thailand

Abstract: Background Scedosporium species are a group of pathogenic fungi, which can be found worldwide around high human-impacted areas. Infections of Scedosporium have been reported in several immunocompromised and immunocompetent patients with a high mortality rate. Recently, we have isolated and identified several Scedosporium strains during an environmental survey in Thailand. Results We describe the isolate, TMMI-012, possibly a new species isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Munoz et al and Cortez et al have previously described S. apiospermum isolates as typically exhibiting floccose, grey to brown colonies with synanamorph graphium, and the absence of cleistothecia in aged cultures [ 52 , 53 ]. Consistent with our findings, Kitisin et al reported that Scedosporium isolates can be identified by their colonies, which are dark grey to smoke brown on the upper surface and dark olive green, brown, or black on the underside along with septate hyphae and solitary conidiophores producing pale brown, ovoid, or ellipsoidal conidia, with an average size of 8.18 ± 0.16 μm, and optimal growth at 37 °C [ 27 ].
Fig.
…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Munoz et al and Cortez et al have previously described S. apiospermum isolates as typically exhibiting floccose, grey to brown colonies with synanamorph graphium, and the absence of cleistothecia in aged cultures [ 52 , 53 ]. Consistent with our findings, Kitisin et al reported that Scedosporium isolates can be identified by their colonies, which are dark grey to smoke brown on the upper surface and dark olive green, brown, or black on the underside along with septate hyphae and solitary conidiophores producing pale brown, ovoid, or ellipsoidal conidia, with an average size of 8.18 ± 0.16 μm, and optimal growth at 37 °C [ 27 ].
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…Notably, in this study, to the best of our knowledge, environmental isolates of Scedosporium species have been discovered for the first time in industrial wastewater in Saudi Arabia. Scedosporium species including S. apiospermum are emerging filamentous fungi characterized by septate hyphae and have previously been isolated in areas heavily impacted by human activity, such as public parks and industrial sites [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…These genes were highlighted in our analyses as anciently shaped traits, and both are associated with stress resistance and adaptation (Campana et al 2022 ; Dubey et al 2020 ; Cordero & Casadevall 2017 ; Gessler et al 2014 ). At the same time, chitin is highly immunogenic and chitin metabolism in Scedosporium and Lomentospora contributes to virulence and resistance to antifungals (Angiolella et al, 2022 ; Kitisin et al 2021 ; Komi et al 2018 ; Pellon et al 2018 ). Melanin is also recognized as a main virulence factor in Lomentospora and Scedosporium spp.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report on CAP treatment of infected tissue or skin models with regard to pro-inflammatory cytokine modulation. So far, only Kitsin et al have reported a decrease in C. albicans growth and reduced secretion of pro-inflammatory cytokines after treatment with an antifungal drug using a cutaneous candidiasis model [46].…”
Section: Discussionmentioning
confidence: 99%